The Analysis of Road Performance on Jalan Gajah Mada Batam, Indonesia - Vendhy Vendhy; Andri Irfan Rifai; Miuhammad Isradi (Indonesian Journal of Multidisciplinary Science, 2022)
Due to the country’s growing vehicle population, major cities in Indonesia are experiencing traffic congestion. Traffic congestion can result in driver delays, inconvenience, economic losses, and air pollution. This paper aims to analyze the road performance on Jalan Gajah Mada (Baloi Indah – UIB) Batam. The method that will be used to analyze the road performance on Jalan Gajah Mada (Baloi Indah – UIB) is MKJI 1997. The standard LOS value in determining the classification of roads in this study is D, or the starting current is unstable, the speed is low and varies, and the volume is close to capacity.